The Chronic Kidney Disease-Epidemiology Collaboration (CKD-EPI) equation does not improve the underestimation of Glomerular Filtration Rate (GFR) in people with diabetes and preserved renal function. Issue 1 (December 2015) - MacIsaac, Richard; Ekinci, Elif; Premaratne, Erosha; Lu, Zhong; Seah, Jas-mine; Li, Yue; Boston, Ray; Ward, Glenn; Jerums, George
Abstract Background Our hypothesis was that both the Chronic Kidney Disease-Epidemiology Collaboration (CKD-EPI) and Modification of Diet in Renal Disease (MDRD) equations would underestimate directly measured GFR (mGFR) to a similar extent in people with diabetes and preserved renal function. Methods In a cross-sectional study, bias (eGFR – mGFR) was compared for the CKD-EPI and MDRD equations, after stratification for mGFR levels. We also examined the ability of the CKD-EPI compared with the MDRD equation to correctly classify subjects to various CKD stages. In a longitudinal study of subjects with an early decline in GFR i.e., initial mGFR >60 ml/min/1.73 m2 and rate of decline in GFR (ΔmGFR) > 3.3 ml/min/1.73 m2 per year, ΔmGFR (based on initial and final values) was compared with ΔeGFR by the CKD-EPI and MDRD equations over a mean of 9 years. Results In the cross-sectional study, mGFR for the whole group was 80 ± 2.2 ml/min/1.73 m2 (n  = 199, 75 % type 2 diabetes). For subjects with mGFR >90 ml/min/1.73 m2 (mGFR: 112 ± 2.0, n  = 76), both equations significantly underestimated mGFR to a similar extent: bias for CKD-EPI: -12 ± 1.4 ml/min/1.73 m2 (p  < 0.001) and for MDRD: -11 ± 2.1 ml/min/1.73 m2 (p  < 0.001). Using the CKD-EPI compared with the MDRD equation did not improve the number of subjects that were correctly classified to a CKD-stage. No biochemical or clinical patient characteristics were identified to account for the under estimation of mGFR values in the normal to high range by the CKD-EPI equation. In the longitudinal study (n  = 30, 66 % type 1 diabetes), initial and final mGFR values were 102.8 ± 6 and 54.6 ± 6.0 ml/min/1.73 m2, respectively. Mean ΔGFR (ml/min/1.73 m2 per year) was 6.0 by mGFR compared with only 3.0 by MDRD and 3.2 by CKD-EPI (bothp  < 0.05 vs mGFR) Conclusions Both the CKD-EPI and MDRD equations underestimate reference GFR values >90 ml/min/1.73 m2 as well as an early decline in GFR to a similar extent in people with diabetes. There is scope to improve methods for estimating an early decline in GFR.